2015
DOI: 10.18632/oncotarget.3699
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxoline impairs tumor progressionin vitroandin vivoby regulating cathepsin B activity

Abstract: Cathepsin B is a ubiquitously expressed lysosomal cysteine protease that participates in protein turnover within lysosomes. However, its protein and activity levels have been shown to be increased in cancer. Cathepsin B endopeptidase activity is involved in the degradation of extracellular matrix, a process that promotes tumor invasion, metastasis and angiogenesis. Previously, we reported an established antibiotic nitroxoline as a potent and selective inhibitor of cathepsin B. In the present study, we elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 54 publications
0
63
0
1
Order By: Relevance
“…19,22 Also, it was discovered that nitroxoline is a potential selective and reversible inhibitor of cathepsin B which results in in vitro and in vivo tumor progression. [23][24][25] The activity of nitroxoline was explained by the inhibition of extracellular and intracellular degradation of the extracellular matrix (ECM), reducing tumor cell spreading. These facts suggest that nitroxoline has great potential as a drug candidate in the treatment of cancer and other diseases connected with increased cathepsin B activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22 Also, it was discovered that nitroxoline is a potential selective and reversible inhibitor of cathepsin B which results in in vitro and in vivo tumor progression. [23][24][25] The activity of nitroxoline was explained by the inhibition of extracellular and intracellular degradation of the extracellular matrix (ECM), reducing tumor cell spreading. These facts suggest that nitroxoline has great potential as a drug candidate in the treatment of cancer and other diseases connected with increased cathepsin B activity.…”
Section: Introductionmentioning
confidence: 99%
“…These facts suggest that nitroxoline has great potential as a drug candidate in the treatment of cancer and other diseases connected with increased cathepsin B activity. [23][24][25] On the other hand, the chemistry of second-row transitionmetal complexes of 1,3,5-triaza-7-phosphaadamantane (pta) and related ligands has attracted much attention due to their potential as water-soluble catalysts. 26,27 These complexes show high stability due to the strong metal-phosphorus bond.…”
Section: Introductionmentioning
confidence: 99%
“…abrogated tumor growth, angiogenesis and metastasis[6].Moreover, silencing of cathepsin B suppressesed the proliferation and invasion of endometrial cancer, suggesting that cathepsin B act as an oncogene [71]. Similar results have been obtained for cysteine cathepsin L. Human melanoma cells, stably transfected with a single chain variable segment from an anti-cathepsin L monoclonal antibody, showed reduced invasiveness in Matrigel as well as diminished metastasis [72].…”
mentioning
confidence: 75%
“…Degradation of extracellular matrix, a major molecular mechanism, was initially proposed to involve cysteine cathepsins in malignant progression [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…ECM is degraded extracellularly predominantly by matrix metallopeptidases, however, the process is greatly accelerated if fragments of ECM proteins are internalized by cancer cells and ultimately degraded within the lysosomes. We and others have shown that inhibition of lysosomal peptidases impairs cancer cell invasion [16][17][18]. Cathepsins, lysosomal cysteine peptidases, are particularly important in this process and can be targeted in the lysosomes by small inhibitors which can enter the cells by diffusion, or by specific protein inhibitors, such as clitocypin and cystatin C. Clitocypin is a fungal inhibitor of cysteine peptidases that shares the same β-trefoil fold as MpL and is an inhibitor of papain-like cysteine peptidases such as papain, cathepsins L, V, S and K, but a weak inhibitor of cathepsin B [19][20][21].…”
Section: Research Papermentioning
confidence: 99%